AOPC 2022: Optical Spectroscopy and Imaging 2023
DOI: 10.1117/12.2651495
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Raman spectroscopy technology for the detection of material composition on the surface of Mars

Abstract: Mars exploration is the biggest hot spot of deep space exploration after lunar exploration, and it is also an important target of manned planetary exploration in the future. For Mars exploration, the detection of its surface material composition is one of the important scientific tasks. This paper mainly introduces a new method for the detection of material components on the surface of Mars -Raman spectroscopy technology, briefly explains the principle of Raman scattering, summarizes the research progress of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In a typical experiment of MoS 2 monolayer epitaxy from its CsCl solution at 850 °C, MoS 2 in CsCl solution was condensed on a sapphire substrate for LPEE (Methods and Figure S1). A home-built high-temperature optical microscope 22 was equipped into the CVD furnace to record the in situ growth process. The in situ optical imaging clearly showed that the MoS 2 flake was growing (with a rate of 1−2 μm/s) as the liquid droplet was moving (Figure 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a typical experiment of MoS 2 monolayer epitaxy from its CsCl solution at 850 °C, MoS 2 in CsCl solution was condensed on a sapphire substrate for LPEE (Methods and Figure S1). A home-built high-temperature optical microscope 22 was equipped into the CVD furnace to record the in situ growth process. The in situ optical imaging clearly showed that the MoS 2 flake was growing (with a rate of 1−2 μm/s) as the liquid droplet was moving (Figure 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%